Rab GTPases in Immunity and Inflammation - Prashar, Akriti; Schnettger, Laura; Bernard, Elliott M.; Gutierrez, Maximiliano G. (Frontiers in Cellular and Infection Microbiology, 2017)
Strict spatiotemporal control of trafficking events between organelles is critical for maintaining homeostasis and directing cellular responses. This regulation is particularly important in immune cells for mounting specialized immune defences. By controlling the formation, transport and fusion of intracellular organelles, Rab GTPases serve as master regulators of membrane trafficking. In this review, we discuss the cellular and molecular mechanisms by which Rab GTPases regulate immunity and inflammation.